Ideological representation of self and other by students and authorities in newspaper reports on students’ protests in selected universities in southwestern Nigeria - Ajayi, Temitope Michael; Ademola, Damilola Isaac (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This study examines language use in press releases by student representatives and authorities of selected Nigerian federal universities on students’ protests, with particular emphasis on the ideological representation of self and other. Data were sourced from online newspaper reports on students’ protests in three randomly sampled federal universities in southwestern Nigeria: University of Ibadan, Obafemi Awolowo University, and University of Ilorin. Data were analysed with insights from van Dijk’s (2004) Critical Discourse Analysis. Findings reveal the discourse is characterised by ideological strategies of positive self-representation and negative other-representation that thrive on discursive moves as lexicalization, negative description of actor’s action, polarization, evidentiality, comparison, number-game, vagueness, counterfactual, categorization, implication, norm expression, and presupposition, among others. While the student representatives depict school authorities as wicked, anti-students’ welfare and oppressive, school authorities project themselves as proactive, efficient, and competent; representing the student representatives as naive, infantile and corrupt.